Bioturbaciones de Tagelus plebeius (Lightfoot, 1786) (Mollusca: Bivalvia) en un ambiente estuárico holoceno (río Quequén Grande, Buenos Aires, Argentina) - de Francesco, Claudio German (2001)
Elongated traces´ showing a lower v-shape closed end have been identified in mid Holocene estuarine deposits exposed along the lower reach of the Quequén Grande River Argentina (38"34´35" S and 58"42´45" W) associated with shells in life position of the infaunal bi´al´e Tagelus plebeius (Líghtfoot). These traces, Iocated in a stratigraphic level dated in circa 6,900 years 14 C B.p, were originated by the burrowing activity of T.  plebeius based upon  the cómparison of their morphological characteristics (width, general shape, colour) with those of T. plebeius and the traces resulting from its burrowing activity at present estuarine environments in the region. The high percentages- of the estuarine gastropod Heleobia aus- tralis (d´Orbigny; found in the sedimentary infilling  of the traces, come from the overlying strata´ abundant Heleobia australis remains. The traces are stratigraphically transgressive within a depth interval of up to 80 cm